Reading problems among vocational students of building construction at Sekolah Menengah Teknik Matang / Piter Linggan @ Peter Bakang - Bakang, Peter Linggan @ Peter (2007)
This study investigated the reading problems faced by vocational school students of Sekolah Menengah Teknik Matang, Kuching, Sarawak. The researcher had observed and interviewed ten (5 Form Four, and another 5 Form Five) students as a mean of pre-assessment procedure to elicit information pertaining to reading problems encountered by vocational students, and had identified the roots of these problems. Sixty students enrolled for the Building Construction course were randomly selected and given questionnaire to fill in. “Reading Problem, Opinion and Suggestion Profile” of each student was composed of information obtained from the Personal Background and Open-ended Questionnaire. The results of this study revealed that students’ reading problems and inefficiency to comprehend reading texts were due to poor vocabulary, poor pronunciation, lack of interests, non-committed and non-motivated. Most problematic, noncommitted and non-motivated readers needed help visualizing what they were reading. To help motivate these readers to enjoy voluntary reading, parents and other relevant parties should encourage children to join “reading circles” and structure reading events to suit children’s current interests.